Micropropagation Of Fig (Ficus Carica) Cultivars ‘texas Everbearing’ And ‘lisa’ & The Anti-hyperglycemic Potential Of Fig Leaves - Tan, Li Vern (2021)
Common figs (Ficus carica) are highly valued fruit crops owing to its elevated nutrient content and vast economic and medicinal importance. Although native to the Middle East and Mediterranean region, the adaptability of figs has attributed to its cultivation also in tropical countries. However, current conventional cultivation methods applied for the propagation of plant stocks are restricted due to the difficulty in obtaining a large number of well-rooted, disease-free plantlets. Plant tissue culture particularly micropropagation has been successfully applied to propagate plant stocks for many commercial crops. The current study aims to establish an efficient protocol for the micropropagation of Ficus carica cv. Texas Everbearing (TE) and Lisa and to evaluate the anti-hyperglycemic potential of fig leaves. From the results obtained, explant surface sterilization was successfully performed with a maximum survival rate of 50%. The optimal shoot induction condition for the cultivar TE was nodal segments cultured horizontally in MS medium supplemented with 1.0 g/L AC, 10 g/L sucrose, 3.0 mg/L TDZ and 0.75 mg/L NAA, recording maximum shoot induction rate (100%), shoot number of 2.15 ± 0.10 shoots and shoot length of 1.05 ± 0.12 cm. For the cultivar Lisa, shoot induction rate of 100%, shoot number of 1.92 ± 0.14 shoots and shoot length of 2.11 ± 0.18 cm was obtained similarly by culturing nodal segments horizontally in MS medium supplemented with 1.0 g/L AC but with 20 g/L fructose, 2.0 mg/L ZEA and 1.0 mg/L NAA. Explants of both cultivars were then successfully rooted in WPM and acclimatized in a potting mix comprising of black soil, red soil and coco peat at a 3:1:1 ratio. In the evaluation of anti-hyperglycemic potential of fig leaves from F. carica cv. TE and Lisa on diabetic induced rats, leaf extracts were obtained via maceration in 50% ethanol for 72 hours. Leaf extract from fig cultivar TE and Lisa at 250 mg/kg showed a significant effect (p < 0.05) in the reduction fasting blood glucose level at day 14 (16.3 ± 2.1 and 17.6 ± 3.1 mmol/L respectively) and average water intake in week 2 (27.2 ± 2.4 and 27.5 ± 2.0 ml/100 g b.w. respectively) when compared to vehicle treated diabetic control, all reflecting a reduction in hyperglycemia. No significant difference was recorded on the body and organ weights when compared to diabetic control rats. This study has successfully documented an efficient micropropagation protocol for fig (Ficus carica) cultivars ‘Texas Everbearing’ and ‘Lisa’ for the production of plant stocks suitable for commercial field establishments and also highlights the potential of fig leaf extract from both fig cultivars in controlling diabetes.